Fatty acid profiles indicate the habitat of mud snails Hydrobia ulvae within the same estuary: Mudflats vs. seagrass meadows - Coelho, H.
Mud snails Hydrobia ulvae occupy different habitats in complex estuarine ecosystems. In order to determine if fatty acid profiles displayed by mud snails can be used to identify the habitat that they occupy within the same estuary, fatty acids of H. ulvae from one mudflat and one seagrass meadow in the Ria de Aveiro (Portugal) were analyzed and compared to those displayed by microphytobenthos (MPB), the green leaves (epiphyte-free) of Zostera noltii, as well as those exhibited by the epiphytic community colonizing this seagrass. MPB and epiphytic diatom-dominated samples displayed characteristic fatty acids, such as 16:1n-7 and 20:5n-3, while 18:2n-6 and 18:3n-3 were the dominant fatty acids in the green leaves of Z. noltii. Significant differences between the fatty acid profiles of H. ulvae specimens sampled in the mudflat and the seagrass meadow could be identified, with those from the mudflat displaying higher levels of fatty acids known to be characteristic of MPB. This result points towards the well known existence of grazing activity on MPB by mud snails. The fatty acid profiles displayed by H. ulvae inhabiting the seagrass meadows show no evidence of direct bioaccumulation of the two most abundant polyunsaturated fatty acids of Z. noltii (18:2n-6 and 18:3n-3) in the mud snails, which probably indicates that either these compounds can be metabolized to produce energy, used as precursors for the synthesis of essential fatty acids, or that the snails do not consume seagrass leaves at all. Moreover, the fatty acid profiles of mud snails inhabiting the seagrass meadows revealed the existence of substantial inputs from microalgae, suggesting that the epiphytic community colonizing the leaves of Z. noltii displays an important role on the diet of these organisms. This assumption is supported by the high levels of 20:5n-3 and 22:6n-3 recorded in mud snails sampled from seagrass meadows. In conclusion, fatty acid analyses of H. ulvae can be successfully used to identify the habitat occupied by these organisms within the same estuary (e.g. mudflats and seagrass meadows) and reveal the existence of contrasting dietary regimes.